The Impact of Childhood Trauma on Adolescent Sexual Health: A Scoping Review - Yuni Fitriya; Dewi Rokhanawati; Askuri (Masters Program in Public Health, 2025)
Background: Violence against children is a serious global problem. The United Nations reports that more than one billion children experience violence every year. Childhood trauma resulting from such violence has a significant impact on adolescent sexual health, increasing the risk of early sexual initiation and sexually transmitted infections. This study aimed to identify the nature and scope of available research literature on the impact of childhood trauma on adolescent sexual health.Subjects and Method: This was a scoping review within the Arkey and O'Maley approach. The framework used in this study employed PCC (population, concept, and context). The population includes adolescents with childhood trauma, the concept focuses on adolescent sexual health, and the context is childhood trauma. The inclusion criteria in this study were primary research articles using English or Indonesian published in the last 10 years (2015 to 2025), full-text articles, and free. Article selection used Rayyan described in the PRISMA Flowchart, and the Critical Appraisal article assessment used Joanna Briggs Institute (JBI).Results: The results of the study, which included a total of 9 articles, stated that childhood trauma in children can be caused by various forms of violence against children, including physical violence, sexual violence, verbal violence, parental divorce, domestic violence, and neglect. All types of childhood trauma are significantly associated with risky health outcomes such as early sex, unmarital sex, teenage pregnancy, being a teenage parent, consuming illegal drugs and alcohol, and early puberty. Each increase in the type of childhood trauma experiences significantly increases risky sexual health.Conclusion: Adolescents who have childhood trauma are more at risk of various types of high-risk health behaviors such as early sexual intercourse, casual sex, teenage pregnancy, becoming teenage parents, at risk of Sexually Transmitted Infections (STIs), early puberty, consuming illegal drugs and alcohol, and committing violence.